2021
DOI: 10.17509/ijcsne.v2i1.38408
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Perceptions, and Attitudes Towards Dementia Among Medical Students in Pakistan

Abstract: The objective of this research was to assess the participants' knowledge and attitudes towards dementia and older people in a broader manner. A Dementia education workshop for undergraduate students was held. Students fill out a questionnaire before and after the workshop.  The Questionnaire was prepared by deep insights into previous literature to determine the knowledge and attitudes of 221 participants towards dementia. Attitudes towards individuals with dementia have shown substantial positive improvements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This study gives additional information regarding medical and health science. Indeed, this will bring more information for futher research in medical and health science as reported in previous reports (Ahsan et al, 2021;Ahsan et al, 2022a;Ahsan et al, 2022b;Ahsan et al, 2022c;Ahsan, 2023;Rana et al, 2022).…”
Section: Resultsmentioning
confidence: 72%
“…This study gives additional information regarding medical and health science. Indeed, this will bring more information for futher research in medical and health science as reported in previous reports (Ahsan et al, 2021;Ahsan et al, 2022a;Ahsan et al, 2022b;Ahsan et al, 2022c;Ahsan, 2023;Rana et al, 2022).…”
Section: Resultsmentioning
confidence: 72%
“…Education has evolved from a knowledge transfer model to an independent, collaborative model influenced by the technology used in higher educational institutions (Abance et al, 2021;Agarry, 2022;Ahsan et al, 2022;Hardiyanti et al, 2023;Abd Mokmin et al, 2023). This has compelled many institutions to reconsider their teaching and learning processes (Shah, 2022;Jadhav et al, 2022;Tiong & Bakar, 2022) (Mendell & Heath, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This contribution highlights the significant importance of education in creating a brighter future for a nation that evolves the extension of education in harmonizing the nation's lifestyle, promotes noble practice in developing positive behavioral maturity, and maintain the needs of psychology in determining minds of act and attitude (Ana, 2020). Mastery of knowledge in education will produce a noble attitude among the nation and cultivate nations' devotion to promoting sustainable national economic growth development as per mentioned in the main vision of Philosophy of National Education and Teacher Education (Idris & Hamzah, 2013;Omar et al, 2020;Ahsan et al, 2022). As in the education system itself, the teacher is one of the important elements that could harmonize the needs of education and plays a great influence in determining the performance of the education system.…”
Section: Introductionmentioning
confidence: 99%